Strong asymptotics for Lp extremal polynomials off a complex curve - Rabah Khaldi (Journal of Applied Mathematics)
We study the asymptotic behavior of Lp(σ) extremal polynomials with respect to a measure of the form σ=α+γ, where α is a measure concentrated on a rectifiable Jordan curve in the complex plane and γ is a discrete measure concentrated on an infinite number of mass points.